Cell patterning for spatially standardized cell biology - Frimat, Jean-Philippe (Technische Universität Dortmund, 2012)
The onus in modern cell biology is on the development of reproducible, develop cell patterning capabilities that are accessible to biologists and to demonstrate new and innovative analytical methods based on the spatial control of cell positioning for widespread cell biology applications as well as fundamental research applications. Plasma stencilling methods for cell patterning were developed which are simple, rapid, inexpensive, reproducible, effective and potentially universal cell line patterning techniques. PDMS micropatterning techniques were also developed to achieve a high resolution patterning capability over large areas and with absolute freedom of design while remaining efficient, cheap, simple and highly reproducible. These features make these methods accessible and desirable to biologists and microengineers alike. As a result from these developments, novel bio-analytical platforms were produced and innovative assays are presented. Cell patterning using these novel techniques was successfully used for the parallel and mass production of 3D spheroids, with high reproducibility and excellent control of the uniformity of spheroid size. A spatially standardized analytical display for high throughput neurotoxicity screening is also presented where cell patterning offers a route to standardize the neurite outgrowth lengths. In addition, a microfluidic system was also used to efficiently pattern and couple single cells by differential resistance pathway principles and validates the concept of using the natural behaviour of cells for mechanical operations within microengineered environments. Taken together, this thesis demonstrates that it is possible to exploit cell micropatterning technologies for the realization of spatially standardized, highly reproducible and quantitative cell biology assays for both fundamental research and commercial applications.
Keywords: Cell patterning; Microfluidics; Neurotoxicity; Spheroids; 660